Implementation of the Kano Model and Importance and Performance Analysis in the Development of a Web-Based Knowledge Management System - Aslamiyah, Suwaebatul (Journal of Information Systems and Technology Research, 2023)
The student department is a work unit that oversees, accommodates and handles various kinds of student activities, both academic and non-academic. The problem that is usually faced by the student department is the occurrence of a knowledge gap (k-gap) between old and new office holders. This problem is caused by the frequent rotation of positions in university departments, while this position rotation is not followed by holding knowledge sharing sessions between employees. The purpose of this research is to develop a web-based knowledge management system for student departments that can overcome the knowledge gap problem. The method used in this research is the Importance and Performance Analysis (IPA) and the Kano Model. The reason for choosing the IPA method is because IPA can be used to measure the value of respondents' mastery of research attributes and can also measure the importance value of an attribute based on the respondent's perception. The Kano model is used in this study because Kano can categorize the attributes of a product or service based on how well the product/service is able to satisfy customer needs. The result of this study is a student department knowledge management system which can reduce the value of the knowledge gap by 1.63 points.